2019
DOI: 10.1142/s0219887819501640
|View full text |Cite
|
Sign up to set email alerts
|

Entropy hemodynamics particle-fluid suspension model through eccentric catheterization for time-variant stenotic arterial wall: Catheter injection

Abstract: Catheterization has an imperative rule in heat transfer investigations, which are frequently applied to analyze and deal with the heart transfer studies. Here, the entering of a catheter adjusts the flow of the blood and it affects the hemodynamic status in the artery region. In practical clinical cases, catheters cannot be precisely concentric with the artery. The impartial of this work is to investigate the behavior of a blood streaming characteristics, in the case of injecting the catheter eccentrically all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The volumetric entropy generation in dimensional form reads as [ 40 , 41 , 42 ] The above equations are comprised of three parts. The first term on the right-hand side represents irreversibility due to heat transfer, the second term shows the irreversibility process due to fluid friction, and the last term shows the behavior of hydromagnetics.…”
Section: Entropy Generation Analysismentioning
confidence: 99%
“…The volumetric entropy generation in dimensional form reads as [ 40 , 41 , 42 ] The above equations are comprised of three parts. The first term on the right-hand side represents irreversibility due to heat transfer, the second term shows the irreversibility process due to fluid friction, and the last term shows the behavior of hydromagnetics.…”
Section: Entropy Generation Analysismentioning
confidence: 99%
“…Mekheimer and Kot [18] presented a particle-fluid suspension model for blood flow through a catheterized curved artery with constriction. The effect of a catheter on entropy generation in two-phase blood flow is analytically studied by Mekheimer et al [19]. Elnaqeeb et al [11] examined the influence of Cu nanoparticles on the flow of blood, assuming the rheology of blood as Newtonian fluid in a catheterized arterial stenosis with a clot.…”
Section: Introductionmentioning
confidence: 99%
“…Ranjit and Shit [23] examined the entropy production on the electroosmotic flow under uniform magnetic field with peristaltic pumping. More studies on the blood flow and entropy generation can be found from the references [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%